2019
DOI: 10.21829/myb.2019.2521773
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta climática de Abies guatemalensis Rehder en Ixtlán de Juárez, Oaxaca, México

Abstract: En México existen especies arbóreas, específicamente, el grupo de las coníferas, las cuales permiten analizar y reconstruir las variaciones climáticas del pasado de una o varias regiones geográficas. El objetivo de este estudio fue determinar el potencial de respuesta dendrocronológica de Abies guatemalensis Rehder a la variabilidad climática en Ixtlán de Juárez, Oaxaca. Se desarrollaron cronologías de madera temprana, de madera tardía y de anillo total de 206 años (1810-2015). El análisis de correlación estac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
2
0
3
Order By: Relevance
“…Therefore, we can infer that the increase in ring width at the high-elevation site may be related to less evapotranspiration due to a lower temperature that occurs at high elevations, and greater retention of moisture in the soil by having flatter reliefs (lesser slopes, Table 1) and deeper soils. The chronologies obtained (Figures 3 and 4) are similar in length to those reported for other Abies species from the TMVB [13,20], however, a chronology from Abies guatemalensis (in all probability being A. hickelii the correct species) in the Sierra Norte de Oaxaca had a reported length of 206 years [21]. Other studies reported chronologies extended for 300 years in Abies guatemalensis from Los Cuchumatanes, Guatemala [40], and for 353 years in Abies concolor from San Pedro Mártir National Park, Baja California [41].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, we can infer that the increase in ring width at the high-elevation site may be related to less evapotranspiration due to a lower temperature that occurs at high elevations, and greater retention of moisture in the soil by having flatter reliefs (lesser slopes, Table 1) and deeper soils. The chronologies obtained (Figures 3 and 4) are similar in length to those reported for other Abies species from the TMVB [13,20], however, a chronology from Abies guatemalensis (in all probability being A. hickelii the correct species) in the Sierra Norte de Oaxaca had a reported length of 206 years [21]. Other studies reported chronologies extended for 300 years in Abies guatemalensis from Los Cuchumatanes, Guatemala [40], and for 353 years in Abies concolor from San Pedro Mártir National Park, Baja California [41].…”
Section: Discussionsupporting
confidence: 73%
“…Carlón-Allende et al [19,20] studied the effect of precipitation and temperature on the radial growth, earlywood, and latewood of Pinus pseudostrobus and A. religiosa in the Monarch Butterfly Biosphere Reserve, Mexico. Aquino-Ramírez et al [21] determined the response of A. guatemalensis Rehder to climatic variability. Villanueva-Díaz et al [22] developed a dendrochronological network for the Armería-Coahuayana basin in southern Jalisco, Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Pese a su alta periodicidad de marcada influencia en México (Pompa- García y Némiga, 2015;Villanueva-Díaz et al, 2015;Aquino-Ramírez et al, 2019). ENOS únicamente influyó de manera significativa sobre el crecimiento radial de los árboles de NEC durante los meses de juniodiciembre Bravo et al, 2018) favorecieron el crecimiento de P. hartwegii en el noreste y occidente de México, al incrementar la cantidad de precipitación recibida en esos sitios, la cual quedó almacenada en el suelo, para posteriormente ser utilizada durante la etapa de reactivación del crecimiento radial de la especie durante marzo-mayo (Biondi et al, 2005).…”
Section: Influencia De Fenómenos Océano-atmósferaunclassified
“…Astudillo Este contraste observado de los resultados obtenidos entre índices de ENOS (MEI e IOS) y los períodos de respuesta significativos en el crecimiento radial de P. hartwegii de los sitios NEC y Pico de Tancítaro (Carlón et al, 2021) pudiera deberse a las variables oceánicas y atmosféricas empleadas en la elaboración de los índices ENOS, de los cuales, IEM es considerado como el más robusto y confiable (Bravo et al, 2018) y es uno de los más empleado en la generación de estudios dendrocronológicos en México (Pompa- García y Némiga, 2015;Villanueva-Díaz et al, 2018b;Aquino-Ramírez et al, 2019;Carlón et al, 2021).…”
Section: Influencia De Fenómenos Océano-atmósferaunclassified
See 1 more Smart Citation